The Ethics Center Lecture Series explores Aztec philosophy - Uribes, Tom::::::::: (2013)
Dr. Alejandro Santana, associate professor of Philosophy and E. John Rumpakis, professor of Hellenic Studies at the University of Portland, will discuss the 'Importance of Aztec Philosophy' for the Ethics Lecture Series.